ANALYSIS OF THE CURRENT STATE AND SPECIES COMPOSITION OF Cichorium intybus L. (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Due to the irrational use of natural resources, some plant species growing on the territory of Kyrgyzstan and playing a prominent role in the life of the Kyrgyz people are on the vergeof extinction. In this regard, the study of the local flora state is one of the urgent tasks of the modern science. The aim of this article is to characterize the cenopopulation, the abundance of speciesand to determine the biological, operational reserves of the medicinal plant Achillea filipendulina,that grows on the northern slopes of the Alai Range and is widely used in the traditional knowledgeof the Kyrgyz people. Defining the prevalence of plants in area under the study was carried outaccording to special criteria. The number (abundance) of species was also assessed. The yield wascalculated using arithmetic formulas. The outcomes of this work can be used in teaching studentsand postgraduates of biological and pharmaceutical specialties, as well as in licensing companiesthat collect medicinal plants.
Keywords: communities, phytocenosis, abundance, area, association, edificators, sub-edifiers, assemblers, slope exposure, raw materials.